Summary Measures of Equalising Income Mobility Based on Three Is of Mobility Curves - Creedy, John; Gemmell, Norman (Journal of Income Distribution®, 2024)
This article extends the ‘Three Is of Mobility (TIM) Curve’ framework, developed by Creedy and Gemmell (2019) to produce summary measures of equalising mobility between two periods, based on areas within the diagram. Two concepts of equalising mobility are considered. The first involves equalisation of incomes in the second period, achieved by a compression of incomes and no re-ranking. The second concept involves maximum redistribution in terms of the inequality of incomes measured over the two periods combined. This involves differential income growth and maximum re-ranking, whereby second-period incomes are ‘swapped’: the richest person becomes the poorest, and so on. The measures are illustrated using a large sample of taxpayers’ incomes in New Zealand.